Health Informatics: Building a Healthcare Future Through Trusted Information : Selected Papers from the 20th Australian National Health Informatics Conference (HIC 2012) - Maeder, Anthony J. Maeder (IOS Press, 2014)
A record of twenty years of productive scientific output is a substantial achievement in any field of ICT, and especially in the youthful domain of health informatics. The Health Informatics Society of Australia, with the active support and involvement of the Australasian College of Health Informatics, is justifiably proud to have sustained the annual Australian National Health Informatics Conference (HIC) series of meetings through to this stage of maturity. As the largest national event of this type in Australia and New Zealand, with a dedicated scientific stream on health informatics, HIC provides a valued platform for academic and research contributions and interchange. It also consolidates the Australasian profile of strong and current research contributions in health informatics, marking our place on the world stage.